Anmeldelser - Müller, Mette (Danish Yearbook of Musicology, 1991)
Review of: Second Conference of the ICTM Study Group on Music Archaeology. Volume l: General Studies / Volume Il: The Bronze Lurs. Editor: Cajsa S. Lund. Publications issued by The Royal Swedish Academy of Music No. 53, Stockholm 1987.